Examining the effects of relative advances in higher mobility roads over higher accessibility roads and income inequality on the relationship between car ownership and economic growth - Poi, Alvin Wai Hoong; Law, Teik Hua; Hamid, Hussain; Mohd Jakarni, Fauzan; Ishak, Siti Zaharah; Ng, Choy Peng (Sage Publications, 2023)
This study examined the effects of relative advances in the ratio of higher mobility roads over higher accessibility roads (MPA) and income inequality on growth of passenger car ownership in relation to economic growth. (MPA is calculated by dividing the total length of higher mobility roads [tolled expressways, national highways, and other main road networks serving medium- to high-speed traffic] by the total length of higher accessibility roads [secondary and regional road networks] in that country in a specific year.) Specifically, we employed the Gompertz function to model changes in the growth rate of car ownership and the income elasticities. The analysis used a panel data between 1963 and 2013 for 53 countries with various income levels. Results revealed that passenger car ownership rate is consistently higher at most of the per capita income levels under mid-range MPA and lower income inequality conditions. As expected, income elasticities were found varied for groups of countries experiencing different MPA and income inequality conditions under different economic developmental levels. Aside from contributing to the highest passenger car growth, the combined effect of mid-range MPA and lower income inequality conditions was also associated with higher income elasticity at higher per capita GDP. In contrast, countries with extreme MPA under higher income inequality conditions generally have the lowest passenger car growth but highest income elasticity at lower per capita GDP. The implications of these findings on private transportation policies relate to measures to control increased car ownership as well as to reduce road casualties.